Transcatheter aortic valve replacement in aortic regurgitation: The U.S. experience. Issue 1 (9th November 2020) - Arora, Shilpkumar; Lahewala, Sopan; Zuzek, Zachary; Thakkar, Samarthkumar; Jani, Chinmay; Jaswaney, Rahul; Singh, Aanandita; Bhyan, Poonam; Arora, Nirav; Main, Anthony; Osman, Mohammed Najeeb; Hoit, Brian D.; et al.
Abstract: Background: Transcatheter aortic valve replacement (TAVR) can be an effective option for high‐risk Aortic Regurgitation (AR) patients. Although international experiences of TAVR for AR are published, U.S. data are limited. This study sought to report the short‐term outcomes of TAVR in AR in the U.S. population. Methods: Study cohorts were derived from the Nationwide Inpatient Sample (NIS) and Nationwide Readmissions Database (NRD) 2016–17. TAVR and AR were identified using ICD‐10‐CM‐codes. The key outcomes were all‐cause mortality, disabling stroke, valvular complications, complete heart block (CHB)/permanent pacemaker placement (PPM), open‐heart surgery, acute kidney injury (AKI) requiring dialysis, and vascular complications. Multivariate logistic regression was used to adjust for confounders. Results: 915 patients from the NIS (male‐71%, age ≥65–84.2%) and 822 patients from the NRD (male‐69.3%, age ≥65–80.5%) underwent TAVR for AR. The median length of stay (LOS) was 4 days for both cohorts. In‐hospital mortality was 2.7%, and 30‐day mortality was 3.3%. Disabling strokes were noted in 0.6% peri‐procedurally and 1.8% at 30‐days. Valve‐related complications were 18–19% with paravalvular leak (4–7%) being the most common. Approximately 11% of patients developed CHB and/or needed PPM in both cohorts. In NRD, 2.2% of patients required dialysis for AKI, 1.5% developed vascular complications, and 0.6% required open‐heart surgery within 30‐days post‐procedure. Anemia was predictive of increased overall complications and valvular complications, whereas peripheral vascular disease was a predictor of increased valvular complications and CHB/PPM. Conclusion: TAVR is a promising option in AR. Further studies are necessary for the expansion of TAVR as the standard treatment in AR.